2000
DOI: 10.1590/s0103-31312000000300004
|View full text |Cite
|
Sign up to set email alerts
|

Soybean seed galactinol synthase activity as determined by a novel colorimetric assay

Abstract: -Galactinol synthase (GS) is a key enzyme for the biosynthesis of raffinose oligosaccharides (RO) which are the flatulence factors present in soybean seeds and several other legumes. Understanding of soybean seed GS properties is, therefore, of biotechnological interest. The GS enzyme catalyses formation of galactinol and UDP from UDP-gal and myo-inositol. This enzyme is currently assayed by an isotopic method. We have then idealized a more convenient method for GS assay based on the indirect colorimetric dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Crude protein extracts from empty vector control cultures lacked this synthetic capacity. The optimal pH, apparent K m and V max for the two GOLS substrates determined for recombinant VvGOLS1 were similar to those reported from other plants (Bachmann et al 1994, Liu et al 1995, Ribeiro et al 2000, Wakiuchi et al 2003, Li et al 2011. The mechanisms involved in the transcriptional regulation of GOLS genes are poorly known.…”
Section: Discussionsupporting
confidence: 73%
“…Crude protein extracts from empty vector control cultures lacked this synthetic capacity. The optimal pH, apparent K m and V max for the two GOLS substrates determined for recombinant VvGOLS1 were similar to those reported from other plants (Bachmann et al 1994, Liu et al 1995, Ribeiro et al 2000, Wakiuchi et al 2003, Li et al 2011. The mechanisms involved in the transcriptional regulation of GOLS genes are poorly known.…”
Section: Discussionsupporting
confidence: 73%
“…Relative expression (%) was determined colorimetrically (Ribeiro et al ., 2000). Error bars correspond to the standard error of the mean.…”
Section: Resultsmentioning
confidence: 99%
“…5 ), which suggests the involvement of other PtrGolS genes in salt- and water-deficit responses, particularly early responses. Many studies have reported that GolS isozymes differ in their enzymatic properties as well as physiological conditions for their activities (Bachmann et al 1994 ; Liu et al 1995 ; Riberio et al 2000 ; Unda et al 2012 ). Further characterization of PtrGolS proteins is thus required to elucidate the roles of GolS in RFO biosynthesis in response to abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Galactinol is synthesized from UDP-D-galactose and myo -inositol by galactinol synthase (GolS; EC 2.4.1.123) (Liu et al 1995 ; Saravitz et al 1987 ). Extensive biochemical studies have characterized GolS in many plant species, including the common bugle ( Ajuga reptans ) (Bachmann et al 1994 ), zucchini squash ( Cucurbita pepo ) (Liu et al 1995 ; Smith et al 1991 ), kidney bean ( Phaseolus vulgaris ) (Liu et al 1995 ), soybean ( Glycine max ) (Riberio et al 2000 ) and cucumber ( Cucumis sativus ) (Wakiuchi et al 2003 ). In addition, molecular biological approaches have accelerated the studies of stress responses of GolS genes.…”
Section: Introductionmentioning
confidence: 99%